The impact of flagrante delicto on the powers of criminal investigation authorities: a comparative study (The International Journal for Scientific Research, 2025)
The study examines the impact of flagrante delicto (being caught in the act of committing a crime) on the exceptional powers granted to criminal investigation officers in the Saudi system and comparative laws. The study aims to establish objective standards and controls for the authority of investigation officers in assessing the availability of sufficient evidence to take criminal action, while ensuring the rights and freedoms of individuals. The study addresses the concept of flagrante delicto, its conditions and cases, and explains that flagrante delicto requires rapid intervention by criminal investigation officers to preserve evidence and prevent tampering with it. It also discusses the exceptional powers granted to investigation officers in cases of flagrante delicto, such as arrest and search, which go beyond the scope of normal powers at the investigation stage. The study also reviews the legal guarantees governing these exceptional powers, and compares the Saudi system with other laws in Arab countries. The study indicates that flagrante delicto gives investigation officers broad powers, but they are restricted by legal controls to protect the rights of individuals. The study concludes the importance of balancing the requirements of achieving criminal justice and protecting personal freedoms, and provides recommendations to enhance the efficiency of criminal investigation officers and their commitment to applicable laws.
Keywords: Flagrante Delicto; Criminal Investigation Powers